Analysis of Financial Performance and Financial Distress of Transportation Companies on the IDX Before and During the Covid-19 Pandemic - Fitri, Annisa Salsabila; Wijayanti, Rahma (Journal of Islamic Contemporary Accounting and Business, 2024)
This study aims to determine the differences in financial performance as indicated by the profitability ratios, namely ROA, ROE and NPM, and the solvency ratio, namely DAR and DER. And also to analyze financial distress or potential bankruptcy of transportation companies on the Indonesia Stock Exchange before and during the Covid-19 pandemic. Method: The method used to measure differences in financial performance is using the Wilcoson Signed Rank Test because the data are not normally distributed. And the method used to analyze financial distress is the Springate method with a descriptive analysis. Result : The results of the analysis of the different Profitability ratio test there are significant differences in the ROA and NPM ratios. And there is no significant difference in the ROE . ratio. The results of the analysis of the Solvency ratio difference test, there is a significant difference in the DAR ratio and there is no significant difference in the DER . ratio. The results of the analysis show that most of the transportation companies on the Indonesia Stock Exchange in 2019 and 2020 as measured by the Springate method have the potential to go bankrupt because as many as 31 companies in 2019 and 2020 are at <0.862.